Simplify use only positive exponents in your final answers
(-3x^2y)^3 (-3x^-3y)^2
(5a^-1b^2)^-2 / 125a^5b^-3
(8x^6y^-3)^1/3 / (2xy)^3
Any help would be greatly appreciated
I will show you all the tools then
YOU apply them
It will help you learn
$\displaystyle (ab)^{n}=a^{n}\cdot{b^{n}}$
$\displaystyle a^b\cdot{a^c}=a^{b+c}$
$\displaystyle \frac{1}{a^b}=a^{-b}$
using this last definition in conjunction with the second one we can see that
$\displaystyle \frac{a^c}{a^b}=a^c\cdot{a^{-b}}=a^{c-b}$
$\displaystyle \sqrt[c]{a}=a^{\frac{1}{c}}$
Apply those..not all are used...it is up to you to figure it out...if you have any specific problems post them and we will help
Good luck
Hello,
Applying the formulas : $\displaystyle (a^b)^c=a^{bc}$ and $\displaystyle a^b a^c=a^{b+c}$
You should get the answers.
$\displaystyle (-3x^2 y)^3 (-3x^{-3} y)^2=(-3)^3 x^6 y^3 (-3)^2 x^{-6} y^2$
$\displaystyle =(-3)^5 x^{6-6} y^5=(-3)^5 y^5=(-3y)^5$
Can you calculate the followings ?
See if this helps
http://www.mathhelpforum.com/math-he...tml#post134788